2005
DOI: 10.1111/j.1468-2982.2005.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity in the Evolution From Migraine to Medication Overuse Headache

Abstract: We set out to study the role of psychiatric comorbidity in the evolution of migraine to medication overuse headache (MOH) by a comparative study of 41 migraineurs (MIG) and 41 patients suffering from MOH deriving from migraine. There was an excess risk of suffering from mood disorders [odds ratio (OR) = 4.5, 95% confidence interval (CI) 1.5, 13.5], anxiety (OR = 5, 95% CI 1.2, 10.7) and disorders associated with the use of psychoactive substances other than analgesics (OR = 7.6, 95% CI 2.2, 26.0) in MOH compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
167
3
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(187 citation statements)
references
References 8 publications
10
167
3
7
Order By: Relevance
“…In the current study, we also found that both anxiety and depression levels were higher in CTTH and MOH, which is consistent with previous reports [24][25][26][27][28]. Moreover, age correlates with the line bisection errors found in the current study were consistent with many previous reports [17], implying an age-related and right-(facial decision task) hemispheric dominant tasks [41].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the current study, we also found that both anxiety and depression levels were higher in CTTH and MOH, which is consistent with previous reports [24][25][26][27][28]. Moreover, age correlates with the line bisection errors found in the current study were consistent with many previous reports [17], implying an age-related and right-(facial decision task) hemispheric dominant tasks [41].…”
Section: Discussionsupporting
confidence: 82%
“…In order to exclude the effect of chronic head pain, we have included a group of patients with CTTH. Bearing in mind that patients with generalized anxiety disorder bisected lines significantly leftward [23], and that both anxiety and depression are comorbid with MOH [24,25] and CTTH [26][27][28], we have used the Zung Self-Rating Anxiety Scale [29] and the Zung Self-Rating Depression Scale [30] to measure the anxiety and depression levels in our participants. the Zung 20-item Self-rating Anxiety Scale [29].…”
Section: Introductionmentioning
confidence: 99%
“…simple cases involve relatively short-term drug overuse, relatively modest amounts of overused medications, minimal psychiatric contribution, and no history of relapse after drug withdrawal. complex cases may involve long-term use of daily opioids or combination analgesics, multiple psychiatric co-morbidities such as personality disorders, addictive disorders and behavior of dependence and/or a history of relapse [17][18][19][20][21] . In the present study BDI scores were not statistically significant different between patients with and without medication overuse.…”
Section: Bdimentioning
confidence: 99%
“…Nem elhanyagolható a pszichológiai kockázati té-nyezők szerepe sem: az anticipátoros szorongás, illetve a hangulatzavar is hozzájárulnak a gyógyszerek túlzott mértékű fogyasztásának kialakulásához, illetve annak fenntartásához. Egy összehasonlító vizsgálat szerint az FTTF-betegek hangulatzavarra vonatkozó kockázata kö-rülbelül ötször, generalizált szorongásra való kockázata hatszor akkora volt, mint a migréneseké [28], és e betegségek a kórkép kialakulását megelőzték. Ugyanebben a vizsgálatban az FTTF-betegek pszichoaktív szerhaszná-latának kockázata csaknem nyolcszorosa volt a migréne-sekének: a szerhasználat a betegek 90%-ában korábbi keletű volt, mint az FTTF.…”
Section: Kockázati Tényezőkunclassified